THE EFFECTS OF BLOOD REHEOLOGICAL ON THE FLOW THROUGH AN AXISYMMETRIC ARTERIAL STENOSIS (Journal of Engineering, 2011)
The prediction of the blood flow through an axisymmetric arterial stenosis is one of the most important aspects to be considered during the Atherosclrosis. Since the blood is specified as a non-Newtonian flow, therefore the effect of fluid types and effect of rheological properties of non-Newtonian fluid on the degree of stenosis have been studied. The motion equations are written in vorticity-stream function formulation and solved numerically. A comparison is made between a Newtonian and non-Newtonian fluid for blood flow at different velocities, viscosity and Reynolds number were solved also. It is found that the properties of blood must be at a certain range to preventing atheroscirasis